2021
DOI: 10.2147/ndt.s296488
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Working Memory Impairment and Neurometabolites of the Prefrontal Cortex in Drug-Naive Obsessive-Compulsive Disorder

Abstract: Purpose This study aimed to investigate the mechanism of working memory (WM) impairment in drug-naive obsessive-compulsive disorder (OCD) by using neuropsychological tests and proton magnetic resonance spectroscopy ( 1 H-MRS). Patients and Methods A total of 55 patients with drug-naive OCD and 55 healthy controls (HCs) were recruited for this study. The working memory (WM) was evaluated using the digit span test (DST), visual space memory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…We postulate that targeting the PFC may be effective in treating OCD. t‐PBM has been shown to modulate the PFC (Holmes et al., 2019; Shahdadian et al., 2022), and studies have found reduced functional connectivity (Li, Hu, et al., 2020) and hypometabolism (Yue et al., 2021) in the PFC of patients with OCD. Other neurostimulation techniques, including TMS (Carmi et al., 2018; Liang et al., 2021; Tzirini et al., 2022), tDCS (Adams et al., 2022; Brunelin et al., 2018), and DBS (Hartmann et al., 2015; Senova et al., 2019), have targeted the PFC in OCD treatment.…”
Section: T‐pbm As a Potential Treatment For Ocdmentioning
confidence: 99%
See 3 more Smart Citations
“…We postulate that targeting the PFC may be effective in treating OCD. t‐PBM has been shown to modulate the PFC (Holmes et al., 2019; Shahdadian et al., 2022), and studies have found reduced functional connectivity (Li, Hu, et al., 2020) and hypometabolism (Yue et al., 2021) in the PFC of patients with OCD. Other neurostimulation techniques, including TMS (Carmi et al., 2018; Liang et al., 2021; Tzirini et al., 2022), tDCS (Adams et al., 2022; Brunelin et al., 2018), and DBS (Hartmann et al., 2015; Senova et al., 2019), have targeted the PFC in OCD treatment.…”
Section: T‐pbm As a Potential Treatment For Ocdmentioning
confidence: 99%
“…The cortico‐striato‐thalamo‐cortical loops, comprising the fronto‐limbic, sensorimotor, ventral cognitive, ventral affective, and dorsal cognitive circuits, play important roles (Shephard et al., 2021). These circuits, involving regions like the PFC, pre‐supplementary motor area (pre‐SMA), orbitofrontal cortex, and nucleus accumbens, are implicated in a range of OCD symptoms from emotional responses and habit formation to reward processing and executive functions (Li, Hu, et al., 2020; Shephard et al., 2021; Yue et al., 2021).…”
Section: T‐pbm As a Potential Treatment For Ocdmentioning
confidence: 99%
See 2 more Smart Citations